Uit: Bro 284/4. Wever en haspelende vrouw. Origineel schilderij in Frans Hals-museum, Haarlem - Rombouts, Gilles, (1656)
Uit: Bro 284/4. Wever en haspelende vrouw. Origineel schilderij in Frans Hals-museum, Haarlem.